Postoperative Megarectum in an Adult Patient with Imperforate Anus and Rectourethral Fistula - Yoshifumi Nakayama; Toshihito Uehara; Masaki Akiyama; Noritaka Minagawa; Takayuki Torigoe; Naohiro Fujimoto (Case Reports in Gastrointestinal Medicine)
This report presents a surgical case of postoperative megarectum in an adult patient with imperforate anus/anorectal malformations. A 71-year-old Japanese male presented with a mass in the lower abdomen which was 15 × 12 × 8 cm in diameter, edema in the right lower extremity, and frequent urination. He had undergone sigmoid loop colostomy for an imperforate anus as a newborn infant. At 28 years of age, the sigmoid loop colostomy was changed to sigmoid divided colostomy in the left lower abdomen. Computed tomography revealed a large cystic mass in the lower abdomen. Retrograde urethrography indicated a rectourethral fistula and megarectum with stones. A small laparotomy incision was created in the right lower abdomen, and the wall of the megarectum was identified. Approximately 2,300 mL of gray muddy fluid was identified and drained. A mucous fistula of the upper rectum was created in the right lower abdomen. This is an extremely rare case of postoperative megarectum in an adult patient with an imperforate anus and rectourethral fistula.